Lasius mixtus - Collingwood, C. A. (Zenodo, 1979)
41. Lasius mixtus (Nylander, 1846) Figs. 149-152. Formica mixta Nylander, 1846b: 1050. Worker. Yellow to brownish yellow; funiculus segments 2 to 5 not longer than broad; scape broadly oval in cross section. Petiole low, narrowing to emarginate dorsal border. Body pubescence coarse but sparse. Body hairs short, longest gaster hairs less than one third maximum hind tibial width. Front tibiae and scape without erect hairs, occasionally present on hind tibiae. Length: 3.5-4.5 mm. Queen. Brownish black; head about as broad as maximum width of alitrunk. Funiculus segments 2 to 6 as broad as long. Scape broadly oval in cross section. Sides of petiole convex with emarginate dorsal border. Body pubescence sparse; microsculpture shallow but coarse. Body hairs short, rather sparse. Front tibiae and scapes without suberect hairs, occasionally one or two present on hind tibiae. Eyes with short hairs between facets. Head width: 1.42-1.68 mm. Length: 6.0-7.5 mm. Male. Dull brownish black; mandibular dentition weak and indistinct. Pubescence sparse, microsculpture coarse with clypeus and frons weakly rugose. Body hairs short, scape and tibiae without suberect hairs. Eyes indistinctly haired. Length: 4.2-4.8 mm. Distribution. Throughout Denmark and South Fennoscandia to 62°. - Throughout the British Isles. - Range: throughout north Eurasia and subalpine regions of Central Europe. Biology. This species nests deep in the ground often among shrub roots and under deep boulders, but occasionally also constructs mound nests of fine loose soil. Alatae fly in August and September and fertilised queens are thought to found fresh colonies through adoption by Lasius alienus and L. niger but actual recorded instances are very few or dubious. Dealate queens are often found wandering singly above ground in spring. Note. L. mixtus was synonymised by Wilson (1955) as one extreme of a variable species L. umbratus (Nyl.). However in North Europe the characteristic L. umbratus with setose appendages is consistently distinct and justifies species ...